Fatigue injury risk in anterior cruciate ligament of target side knee during golf swing - Purevsuren, T.; Kwon, M. S.; Park, W. M.; Kim, K.; Jang, S. H.; Lim, Y.-T.; Kim, Y. H. (Journal of Biomechanics, 2017)
A golf-related ACL injury can be linked with excessive golf play or practice because such over-use by repetitive golf swing motions can increase damage accumulation to the ACL bundles. In this study, joint angular rotations, forces, and moments, as well as the forces and strains on the ACL of the target-side knee joint, were investigated for ten professional golfers using the multi-body lower extremity model. The fatigue life of the ACL was also predicted by assuming the estimated ACL force as a cyclic load. The ACL force and strain reached their maximum values within a short time just after ball-impact in the follow-through phase. The smaller knee flexion, higher internal tibial rotation, increase of the joint compressive force and knee abduction moment in the follow-through phase were shown as to lead an increased ACL loading. The number of cycles to fatigue failure (fatigue life) in the ACL might be several thousands. It is suggested that the excessive training or practice of swing motion without enough rest may be one of factors to lead to damage or injury in the ACL by the fatigue failure. The present technology can provide fundamental information to understand and prevent the ACL injury for golf players.